A current view on the involvement of protein phosphatase PP2A subunits in the responses of plants to abiotic stress at the subcellular level - Csaba Máthé; Márta M-Hamvas; Tamás Garda; Zoltán Kónya (Plant Cell Reports, 2026)
PP2A is the most abundant member of the non-metal-dependent serine-threonine phosphatases in eukaryotes. It is an important player in the reversible phosphorylation of proteins and involved in a wide variety of cellular processes, from signal transduction events to cell cycle regulation and a large number of metabolic processes. At the subcellular level, there is a comprehensive knowledge on PP2A-mediated regulation of chromatin and cytoskeletal organization and there is increasing evidence for its relevant functions in the organization of membrane compartments. Relatively little is known about the related regulatory functions of this enzyme complex in the responses of plants to abiotic stresses. However, recent research has revealed several aspects of these relationships at the subcellular level, mainly for osmotic/salt and heat stress. PP2A is a family of three-subunit holoenzyme complexes, where “A” are scaffolding, “B” are regulatory and “C” are catalytic subunits. Here we discuss the involvement of all these subunits in the regulation of stress-related changes in chromatin, cytoskeleton (microtubule and microfilament), endomembrane (including ER) and plastid/mitochondrial organization and emphasize how they sustain the functioning of plant cells under multiple abiotic stresses. There are crucial subunits in this respect, for example A1, C3 and C4 as well as “B” regulatory subunits such as FASS and members of the B and B’ subfamilies. PP2A is involved in stress hormone (featuring ABA) signaling at multiple levels. In light of recent research, we show that different PP2A holoenzymes link together diverse stress-related signaling mechanisms.